Comparing Routine Protocol Versus Abbreviated Protocol in Reaching Radiological Diagnosis of Stroke Using Magnetic Resonance Imaging (MRI) - ALSawyan, Ashjan Sulaiman (British Journal of Healthcare and Medical Research, 2022)
Background: Magnetic Resonance Imaging provides information that's beneficial for diagnosing ischemic stroke, choosing proper patients for thrombolytic therapy, as well as predicting the prognosis of ischemic stroke. Objectives: To evaluate the efficacy of the routine protocol of MRI and Abbreviated term protocol. The goal is to compare both types of protocols in the developing sustainable and reliable medical imaging for an effective radiological diagnosis of the cerebrovascular strokes. Methodology: This is a retrospective study conducted at PSMMC hospital to compare abbreviated with routine protocol in radiological diagnosis of acute stroke using Magnetic Resonance Imaging. An overall 116 patient aged from 40 – 95 years data were gathered who had previously undergone diagnosis using a routine protocol. They were provided to the board-certified radiologist in all of our 10 radiologists with different years of experiences who have performed the process. Therefore, image acquisition was the standardized method that has been conducted following the national quality assurance. The data was analysed using a variety of descriptive and inferential statistical measures. SPSS 12.0 was used to analyse the information gathered. Results: The results expressed that the sensitivity measure of the abbreviated protocol concerning the routine protocol ensured that 87 patients were evaluated to be positively diagnosed with the presence of acute strokes, with the progress rate and average frequency of 95.6%, after the application of abbreviated protocol. On the other hand, the results also elaborated those 25 patients who were not diagnosed initially for the presence of stroke using the medium of routine protocol for MRI, expressed the similar results with the abbreviated protocol as well. These patients presented no significant signs of having the strokes and associated with the abbreviated protocol, presenting an average success rate of 100%. Conclusion: The study ensured that the MRI performed using the abbreviated protocol expressed similar diagnostic results as the routine protocol, confirm the presence of the acute strokes among the patients. The specificity and sensitivity test indicated that the sustainable and expressive dependability and reliability of both types of MRI protocols.